Decision theory applied to the stock market - Low, Seng Hoom (Nanyang Technological University, 2022)
It is not uncommon to hear advice from others saying “Go invest your money, leaving it in the bank is useless” or “I regretted not investing earlier on when I was younger”. In this paper, I aim to defend the idea that it is irrational to not invest in the stock markets, or any alternative financial derivative or investment. In the initial section, I will set out to identify and explain the related concepts and theories of money, by looking at the Ontology of Money as well as cryptocurrencies and Non-Fungible Tokens. I will then offer an economic justification upon exploring the main criticisms and advocates of profit. Thereafter, I will attempt to give an outline of the United States’ financial market structure, explore the act of ‘short selling’ and the conflict of interest of the various parties involved. With the various related financial concepts and theories in place, I will then apply decision theory to explore various scenarios in recent market developments including the short selling phenomena as well as the game theory outlook by individual investors. Overall, I conclude that it is rational to invest in the markets as people will be better off doing so than not.